2022
DOI: 10.1097/cmr.0000000000000836
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in toll-like receptor 3 and 4 genes as prognostic and outcome biomarkers in melanoma patients

Abstract: Melanoma is one of the most aggressive tumors, and in the setting of rising incidence and mortality, there is an urgent need to identify new prognostic markers. Toll-like receptors (TLRs), are aberrantly expressed in numerous cancers, including melanoma. TLR signaling provides a microenvironment that is involved in antitumor immune response, chronic inflammation, cancer cell proliferation and evasion of immune destruction. In the present study, we investigated whether single nucleotide polymorphisms (SNPs) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
(96 reference statements)
0
0
0
Order By: Relevance
“…The study population included 120 patients, and the genotyping was carried out employing TaqMan real-time PCR assay. The TLR4 D299G and T399I variants were associated with nodal metastasis, advanced stage III, and severity of melanoma [ 27 ]. A very recent study by Jha and colleagues demonstrated that the AG genotype and the G allele were found to be the risk genotype and risk allele in the population studied.…”
Section: Discussionmentioning
confidence: 99%
“…The study population included 120 patients, and the genotyping was carried out employing TaqMan real-time PCR assay. The TLR4 D299G and T399I variants were associated with nodal metastasis, advanced stage III, and severity of melanoma [ 27 ]. A very recent study by Jha and colleagues demonstrated that the AG genotype and the G allele were found to be the risk genotype and risk allele in the population studied.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, increasing evidence has suggested that these DAMPs can serve as powerful immunological adjuvants, eliciting antitumor immunity and increasing anticancer therapy efficacy (11,12,15,23). However, SNPs in PRRs can alter receptor function to affect the immune response and therapeutic response (17,20,21,(26)(27)(28)(29). For example, RAGE G82S is associated with chemotherapy response and clinical outcomes in non-small cell lung cancer, while P2RX7 E496A is related to overall survival outcome in chronic lymphocytic leukemia patients (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas TLR4 D299G and T399I polymorphisms were associated with melanoma severity, nodal metastases, and advanced stage III and could be then potential markers targeting the survival and prognostic of melanoma patients. TLR4 T399I polymorphism was highly correlated with worse survival [130]. However, no association between TLR7 single nucleotide G pp.…”
Section: Melanomamentioning
confidence: 95%